TEACHING METHODS: SUGGESTOPEDIA - Палымбетова Дилбар Турсынбаевна (Journal of new century innovations, 2022)
Annotation: The aim of this article giving information about suggestopedia which is considered one of the most modern teaching methods. Advantages and disadvantages as well as history of this method is also will be defined.